Development of Spiritual Nuances Modules in form of Comic Strip on Human Reproductive System Material for Student Grade XI - Riri Apriyanti; Lufri Lufri; Dwi Hilda Putri (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2018)
The purpose of this research is to develop a module of spiritual nuance in the form of comic strips on reproduction material for students of class XI SMA / MA valid and practical. This research uses 3 of 4 stages 4D models that is define, design and develop. The developed product will be validated by 3 validators including 2 lecturers of biology and 1 biology teacher of SMAN 4 Padang, while for practicality will be done by 32 students of SMAN 4 Padang. The data of this study include the primary data obtained from the questionnaire filled directly by the subject of research. Based on the results of the study obtained the validity of 91.30% with very valid criteria, practicality by teachers 86.68% practical criteria and practicality by students 88.56% with practical criteria.